Answer:
Following are the solution to this question:
Step-by-step explanation:
Please find the complete question in the attached file.
In the given equation, when the point t=0
So,
[tex]\to r(0) = (3 \cos 0)i + (0^4 - 6 \sin 0)j + (2e^{3\times 0})k)[/tex]
[tex]= (3 \times 1)i + (0 - 0)j + (2e^{0})k)\\\\ = 3i + 0j + (2 \times 1)k)\\\\ = 3i + 0j + 2k \\[/tex]
The value of the coordinates are [tex]3, 0, 2[/tex] . so, the equation of the line is:
[tex]\to \frac{(x-3)}{3 \cos \ t} = \frac{(y-0)}{(t^{4}-6 \sin \ t)} = \frac{(z-2)}{2e^{3t}}=k[/tex]